The diagnostic potential of MicroDTTect compared to conventional culture of tissue samples in orthopedic infections - Giannetti, Alessio; Romano, Jacopo; Fidanza, Andrea; Di Mauro, Michele; Brunetti, Mauro; Fascione, Fabrizio; Calvisi, Vittorio (Lo Scalpello - Journal, 2022)
Objective. The evolution of new prosthetic and osteosynthesis devices has led to better outcomes and therefore more frequent surgical indications. As a consequence, an increased incidence of complications such as infections or aseptic loosening in orthopedic and trauma surgery are being recorded in general population. MicroDTTect is a quick and simple system that is useful to detect low grade or bio-film related infections. The aim of this study was to evaluate the reliability of MicroDTTect in detection of orthopedic infections compared to conventional culture of tissue samples. Methods. The population enrolled was composed of 13 patients undergoing surgery for prosthesis or osteosynthetic device failure or loosening. The MicroDTTect system and traditional culture of tissue samples were applied to identify the pathogens and compared with each other. Results. MicroDTTect had a higher sensitivity compared to conventional culture of tissue samples. Two cases resulted positive while the traditional culture sample showed a false negative result. In addition, with MicroDTTect a polymicrobial infection was identified, while with traditional methods was misdiagnosed. Conclusions. We showed that treatment of suspected implant infections using the MicroDTTect device improves microbiological diagnosis with more sensitive results, leading to a more accurate treatment.